Menstruation Matters Challenging the Law's Silence on Periods. - Crawford, Bridget J. (New York University Press, 2022)
Explores the burgeoning menstrual advocacy movement and analyzes how law should evolve to take menstruation into account.Approximately half the population menstruates for a large portion of their lives, but the law is mostly silent about the topic. Until recently, most people would have said that periods are private matters not to be discussed in public. But the last few years have seen a new willingness among advocates and allies of all ages to speak openly about periods. Slowly around the globe, people are recognizing the basic fundamental human right to address menstruation in a safe and affordable way, free of stigma, shame, or barriers to access.Menstruation Matters explores the role of law in this movement. It asks what the law currently says about menstruation (spoiler alert: not much) and provides a roadmap for legal reform that can move society closer to a world where no one is held back or disadvantaged by menstruation. Bridget J. Crawford and Emily Gold Waldman examine these issues in a wide range of contexts, from schools to workplaces to prisons to tax policies and more. Ultimately, they seek to transform both law and society so that menstruation is no longer an obstacle to full participation in all aspects of public and private life.